What a Neurosurgeon Should Know about the Endolymphatic Sac: Part 1–Anatomy and Physiology - Vaz, Marco Antônio Schlindwein; Monteiro, Jander; Braga, Francisco Luiz Souza; Lavinsky, Joel; Santis, Giuseppe Casella; Becker, Lia Grub; Rocha Filho, Marcelo Assis Moro da; Ribas, Carmen Austrália Paredes Marcondes; Araújo, Ricardo Marques Lopes de; Figueiredo, Eberval Gadelha; Isolan, Gustavo Rassier (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Objective To describe the microsurgical anatomy and the physiology of the endolymphatic sac (ES) that a neurosurgeon should know.Methods Review of previous studies from 1927 to 2021, from basic and translational research using human and animal ES tissue or cells, as well as previous reviews about the subject. The present article is divided into three parts. In this first part, we review the microsurgical anatomy and physiology of the ES.Results The ES is a structure situated in the inner ear, together with the cochlea, the vestibular system, and other structures. Differently from its adjacent structures, the ES does not have a specialized epithelium; instead, it has mitochondria-rich cells and ribosomal-rich cells, which are responsible for ionic transportation and secretory activity. Apart from these functions, the ES is also responsible for homeostasis regulation of the inner ear, endolymphatic fluid volume control, immune response, elimination of inner ear cellular debris and floating otoconia, regulation of membranous labyrinth pressure, acid/basic transport, and secretion of substances. Its anatomy is not very variable, since in most studies no more than 20mm separates the location of the ES in the samples, in any direction.Conclusion The human ES has vital functions in the inner ear, and its anatomy is rarely variable. Knowing that, and the importance of this area for neurosurgery, the present study elucidates the exact location of the ES and the lost functions that a lesion in this structure must cause.
Keywords: endolymphatic sac; anatomy; physiology; neurosurgery